2020
DOI: 10.22452/jscp.vol11no1.6
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Confronting Nigeria Indigenous Construction Enterprise

Abstract: Construction activities in Nigeria are dominated by foreigners’ managed construction enterprises. These companies constitute less than 5 percent of the number of construction enterprises in Nigeria; however, they are involved in over 95 percent of high net-worth construction activities. Nigeria Indigenous Construction Enterprises (NICE) are faced with numerous challenges that have limited their performances. This makes construction clients to patronize foreigners’ managed construction firms because of the flaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Nigeria saw foreign contractors dominate larger projects [14], while local contractors struggled with profit loss, late payments, poor tendering practices, and inadequate skills.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nigeria saw foreign contractors dominate larger projects [14], while local contractors struggled with profit loss, late payments, poor tendering practices, and inadequate skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies [6], [7], [8], [9], [10], [11], [12], [13], [14] have aimed to highlight two main points: the significance of increased local involvement in developmental projects and the examination of obstacles hindering such participation. However, there appears to be minimal scholarly effort in uncovering the underlying phenomena, strategies, and mechanisms crucial for enhancing local contractor engagement in public sector projects.…”
Section: Introductionmentioning
confidence: 99%
“…It was also discovered that ICFs had significant rates of time overruns (traditional: 34-146 percent; non-traditional: 45-60 percent), and cost overruns (traditional: 35-47 percent; non-traditional: 31-36 percent). According to the study by Akinsiku (2020), the most significant obstacles for ICFs and contractors includes a lack of technical experience, unsatisfactory turnover on projects, and delays in disbursement of funds to subcontractors for work done. The most important measures of enhancing ICFs' performance were the application of project management techniques in building operations, quality control of materials, and boosting delivery capacity.…”
Section: Performance Index Of Both Expatriate and Indigenous Construc...mentioning
confidence: 99%
“…This preference for expatriate is as a result of the perceived quality performances expected of the expatriate which is largely lacking the performances prevalent to the local contractors. Consequently, the poor performances of these indigenous contractors was emphasized by the study of Akinsiku (2020), who suggested delays in meeting project completion time, reduced quality of work and insufficient capital leading to bankruptcy as the poor performance related factors prevalent to this indigenous contractors.…”
Section: Performance Index Of Both Expatriate and Indigenous Construc...mentioning
confidence: 99%